Dose–response relationship between physical activity and cardiometabolic risk in obese children and adolescents: A pre-post quasi-experimental study - Chen, Zekai; Zhu, Lin (Frontiers in Physiology, 2023)
Objective: This study aims to explore the dose-response relationship between the daily duration of moderate to vigorous physical activity and the improvement of cardiometabolic risk indicators in obese children and adolescents. Methods: Seventy-seven obese children and adolescents aged 10–17 years were randomly recruited for a 4-week exercise intervention in a closed camp during 2019–2021, physical activity was monitored by ActiGraph GT3X + to obtain daily MVPA duration, and the improvement of CMR indicators were reflected by the changes (Δ) of waist circumference, systolic blood pressure, diastolic blood pressure, total cholesterol, triglyceride , high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, fasting insulin, fasting plasma glucose, and homeostasis model assessment of insulin resistance before and after the intervention, calculated as ‘‘Δ+indicator” = values after intervention–values before intervention. The groups were divided into different doses of Q1∼Q3 according to the daily MVPA duration from low to high. The differences in the improvement of different dose groups were compared by one-way analysis of covariance, and the dose-response relationship between MVPA duration and CMR indicators improvement was analyzed by linear regression and piecewise regression. The nonlinear relationship was analyzed by restricted cubic spline. Results: 1) Compared with indicators before the intervention, WC, SBP, DBP, TC, TG, HDL-C, LDL-C, FINS, and HOMA-IR were significantly lower after the intervention (p-value < 0.05). 2) The dose-response relationship between MVPA and LDL-C improvement was non-linear (P-Nonlinear < 0.05). When MVPA >77.1min/day, ΔLDL-C further decreased with the increase of MVPA duration [β = −0.009, 95% confidence interval (CI): −0.013, −0.005], and when MVPA ≤77.1min/day, increasing the MVPA duration did not increase the improvement of ΔLDL-C. Conclusion: There was a nonlinear dose-response relationship between the daily MVPA duration and LDL-C improvement in obese children and adolescents. In order to obtain more significant improvement in LDL-C through increased MVPA duration, MVPA duration should be higher than 77.1 min/day.